Ecosystem services and water quality of turloughs, a form of intermittent karst wetland - Delle Grazie, Fabio Massimo (Trinity College Dublin. School of Engineering. Disc of Civil Structural & Environmental Eng, 2023)
Ecosystem services (ES) can be defined as the conditions and processes through which natural ecosystems sustain and fulfil human life. These can be classified as provisioning, regulating, and cultural (water and raw material provision, flood risk attenuation, carbon sequestration, ecotourism). The quantification of ES can help analyse different scenarios linked to pressures on natural ecosystems (such as wetlands) like road drainage schemes, water supply and wastewater disposal. Turloughs, the focus of this study, are a kind of ephemeral lake/wetland which are present mostly in Ireland and show periodic inundation and lacustrine deposits. They are flooded for some periods across the year (typically in the winter) but usually dry up in summer months. Turloughs are protected under the Water Framework Directive (WFD, Directive 2000/60/EC) and the EU Habitats Directive (92/43/EEC). Their ES had never been quantified before. The aim of this study was therefore to quantify the ES of turloughs and compare these to the literature on the ES of similar ecosystems. Fifty-five turloughs were initially surveyed to assess their water quality and successively give an indication of their ES by applying the framework developed in this thesis. Seven turloughs (Blackrock, Lough Coy, Lough Aleenaun, Lough Gealain, Caranavoodaun, Skealoghan, Coolcam) were then selected from a previous study, to be representative of different hydrological regimes and a wide range of physico-chemical and chemical characteristics. They are located in the west of Ireland, in Counties Clare, Roscommon, Galway and Mayo. The majority of the fifty-five turloughs have mesotrophic waters (33), while 7 of them have oligotrophic waters, 11 have eutrophic waters and 4 hypertrophic. Water chemico-physical parameters (temperature, pH, dissolved oxygen, turbidity, and redox potential were measured in-situ, while others (alkalinity and colour), together with carbon and nutrient species (total phosphorus, soluble reactive phosphorus, total nitrogen, total oxidized nitrogen, dissolved inorganic carbon, dissolved organic carbon, colour) were determined by the appropriate laboratory methods. pH, carbon and nutrient species (total carbon and nitrogen, phosphorus and organic carbon) were also determined on soil samples taken from the turlough catchment during the dry phase. Greenhouse gas emissions (carbon dioxide, methane and nitrous oxide) were determined using the closed chamber method during both the wet and dry phases of the turloughs. This study provides a quantification and valuation of the ES of turloughs, which had never been done before. The seven turloughs studied display a variety of hydrological characteristics, habitats, soils and vegetation and therefore ES of different quality and value; each ES was quantified using appropriate models. The most important ES for these turloughs are flood mitigation, habitat preservation and ecotourism. The calculated monetary values (from ? 35,556 ha-1 yr-1 to ? 122,150 ha-1 yr-1) are in line with the literature on ES provision for similar habitats, but some of the turloughs show also significantly higher values. Though their ecohydrological condition has, in general, been assessed to be relatively stable compared to a previous study dating to about ten years ago, there are threats from anthropogenic activities and climate change that could cause a degradation of their habitats and the ES they provide. The monitoring of their waters to detect any nutrient enrichment is especially important for the oligotrophic ones, which have a high biodiversity value. There are opportunities to enhance ES values and thereby promote a better ecohydrological state for the rest of them, for example by lowering nutrient emissions in the zones of contribution of the turloughs. This could entail also the study of the socio-economical local situation, as turloughs are deeply integrated in the local socio-economical structure. A framework has been proposed, which requires field data that can be integrated with literature data, depending on the availability and the level of depth of the studies. Indicators can be used when field data are not available. In particular, land cover, soil type, and vegetation cover are examples of parameters linked to the provision of ES and that can be acquired from existing literature or from remotely sensed images. Due to the variability of several chemico-physical and chemical parameters, a single sample taken near the maximum flooded stage has been shown not to be representative of the whole variability during a hydrological year. Samples with at least a seasonal frequency should therefore be taken. The study of further turloughs with the framework proposed in this thesis would help to have a more complete picture of the ES provided by these features which are almost unique to Ireland.
APPROVED
Keywords: turloughs; wetlands; ecosystem services; water quality